Prevalence of bovine fasciolosis in Jalingo abattoir, Taraba State, Nigeria - Tochukwu Obialigwe; Halima Pindar; Iranyang Uko; Kingsley Ekechukwu (Microbes and Infectious Diseases)
Background: Bovine fasciolosis causes significant economic losses to farmers and herders in Africa. The study aimed at determining how often bovine fasciolosis occurs in Jalingo abattoirs. Methods: This study was conducted in Jalingo abattoir using retrospective records from the year 2012 to 2021 and a prospective abattoir meat inspection survey to evaluate the prevalence and seasonal variation of bovine fasciolosis in Jalingo, Taraba State, Nigeria. Results: An overall bovine fasciolosis prevalence of 8.29% was observed in 149,611 cattle slaughtered at the abattoir. There was statistical significance (p < 0.05) between seasons and bovine fasciolosis occurrence, with the rainy season having a slightly higher prevalence. Additionally, the prospective study analyzed 2424 cattle during the months of March and April 2022 at the Jalingo abattoir. Cows had a higher infection rate (6.15%) than bulls (2.43%), although the prospective study had a bovine fasciolosis prevalence of 8.58 percent. Bovine fasciolosis occurrence was shown to have a significant association with age, with a higher prevalence in older cattle (5.82%) compared to younger cattle (2.76%). However, there was no association that could be considered statistically significant between infection rates and the breed or sex of the slaughtered cattle. Conclusion: Both investigations, retrospective and prospective, shed light on the frequency and seasonal fluctuations of bovine fasciolosis in the research area. These insights can be utilised as a basis for further design considerations in future studies aimed at eradicating the disease or reducing its prevalence in the cattle herd and boosting livestock health and productivity.